Synthesis and conformational analysis of a simplified inositol-model of the Streptococcus pneumoniae 19F capsular polysaccharide repeating unit. (18th April 2017) - Catelani, Giorgio; D'Andrea, Felicia; Guazzelli, Lorenzo; Griselli, Alessio; Testi, Nicola; Chiacchio, Maria Assunta; Legnani, Laura; Toma, Lucio
Abstract: Carbohydrate mimics have been studied for a long time as useful sugar substitutes, both in the investigation of biological events and in the treatment of sugar-related diseases. Here we report further evaluation of the capabilities of inositols as carbohydrate substitutes. The conformational features of an inositol-model of a simplified repeating unit corresponding to the capsular polysaccharide of Streptococcus pneumoniae 19F has been evaluated by computational analysis, and compared to the native repeating unit. The inositol mimic was synthesized, and its experimental spectroscopic data allowed for verification of the theoretical results. Graphical abstract: A further insight into the feasibility of employing inositols as sugar mimics has been presented. The conformational behaviour of a simplified inositol-model of the repeating unit of Streptococcus pneumoniae 19F capsular polysaccharide has been analysed. Highlights: The possibility to use inositols as carbohydrate mimics has been investigated. An inositol-model of a simplified Streptococcus Pneumoniae 19F capsular polysaccharide repeating unit has been synthesized. The conformational behaviour of the inositol-model has been evaluated.